Study Of A Geotechnical Evaluation Of Termite Mound Clay As A Potential Replacement Of Bentonite In Developing Low Permeability Soil Mix - Nur Aishah Mohammad Zanwa (School of Environmental Engineering, Universiti Malaysia Perlis, 2016)
The objectives of this study listed as follow to analyse the permeability and shrinkage of soil mix between Termite Mound Clay and Bentonite. To compare the potential of termite mound clay as replacement of Bentonite.